Evaluation of Pavement Ride Quality on Road Networks Using Smartphone Application - Azizan, Mohd Sazwan; M. N. M. Taher, (Recent Trends in Civil Engineering and Built Environment, 2021)
The problems of surface pavement failure on the road are highly affects the road users. It leads to increase the travel time, decrease the comfort and safety of passengers, decrease traffic flow of neighbors, expose the vehicle owners for additional maintenance cost, traffic congestion and also affect economic growth and forebode of tourism in the study area. This study aims to evaluate the roughness value of the road surface using the International Roughness Index (IRI) method. Several site locations were selected at Jalan Kuala Kedah, Jalan Anak Bukit, Jalan Langgar, Jalan Kangar-Alor Setar, Jalan Pendang-Tanah Merah, Jalan Datuk Kumbar, Jalan Alor Mengkudu, Jalan Titi haji Deris, Jalan Tualang, and North-South Expressway Roadbounce application available in the smartphone was employed to measure the level of roughness for the road surface. The results of field measurement recorded that all three of the road networks have the roughness index that falls into the acceptable scale according to standard ASTM E1926 and fulfills the requirement from Public Work Department (PWD). These findings facilitate road surface assessment work to provide a better riding quality, minimum delays at road works, and enhance deformation resistance.